The value of computed tomography perfusion deficit volumes in acute isolated brainstem infarction - Chen, Pengjun; Pan, Yiying; Wang, Jingke; Hui, Junguo; Gao, Ruijie; Lin, Guihan; Li, Bingrong; Rao, Jie; Xia, Shuiwei; Ji, Jiansong (Frontiers in Neurology, 2023)
Purpose: Diagnosis of acute isolated brainstem infarction is challenging owing to non-specific, variable symptoms, and the effectiveness of non-contrast computed tomography (NCCT) is poor owing to limited spatial resolution and artifacts. Computed tomography perfusion (CTP) imaging parameters are significantly associated with functional outcomes in posterior circulation acute ischemic stroke; however, the role of CTP in isolated brainstem infarction remains unclear. We aimed to determine the value of CTP imaging parameters in predicting functional outcomes for affected patients.In total, 116 consecutive patients with isolated pontine/midbrain hypoperfusion who underwent CTP and follow-up by magnetic resonance imaging (MRI) between January 2018 and March 2022, were retrospectively analyzed. Perfusion deficit volumes on all maps, and the final infarction volume (FIV) on MRI were quantified. "Good" functional outcome was defined as a 90day modified Rankin Scale score of 0 and 1. Statistical analysis included uni-and multivariate regression analyses, binary logistic regressions, and receiver operating characteristics (ROC) analyses.Results: In total, 113 patients had confirmed isolated pontine/midbrain infarction on follow-up MRI.Onset-to-scan time, visibility of ischemic lesions on NCCT, the baseline National Institutes of Health Stroke Scale (NIHSS) score, and perfusion deficit volumes on all CTP maps were significantly associated with FIV (P<0.05). In a multivariate linear regression model, adjusted for age, sex, NIHSS score, onset-to-scan time, and visibility of NCCT, perfusion deficit volumes remained significantly associated with FIV. In binary logistic regression analyses, perfusion deficit volumes on all CTP maps remained independent predictors of a good functional outcome. In ROC analyses, the cerebral blood flow deficit volume showed a slightly higher discriminatory value with the largest area under the curve being 0.683 ([95% CI, 0.587-0.780], P=0.001).Perfusion deficit volumes of CTP imaging could reflect the FIV and contain prognostic information on functional outcomes in patients with acute isolated brainstem infarction.